Effects of linagliptin on renal endothelial function in patients with type 2 diabetes: a randomised clinical trial - Ott, Christian; Kistner, Iris; Keller, Mirjam; Friedrich, Stefanie; Willam, Carsten; Bramlage, Peter; Schmieder, Roland (Diabetologia, 2016)
Endothelial dysfunction predicts cardiovascular damage and renal involvement. Animal experiments and human studies indicate an increased nitric oxide (NO) activity and endothelial NO synthase (NOS) expression in the early stage of type 2 diabetes. The aim of the study was to assess the effect of linagliptin on the endothelial function of the renal vasculature.In this randomised, double-blind, parallel-group, investigator-initiated trial, 62 patients with type 2 diabetes were randomly assigned (by computer-generated random code) to receive linagliptin 5 mg (n = 30) or placebo (n = 32) for 4 weeks. The primary objective was to assess endothelial function of the renal vasculature, by constant-infusion input-clearance and urinary albumin/creatinine ratio (UACR), both before and after blockade of NOS with N (G)-monomethyl-L-arginine (L-NMMA).Treatment with linagliptin for 4 weeks reduced fasting, postprandial blood glucose and HbA1c, although not significantly; no change occurred with placebo. Renal plasma flow (RPF) did not change after linagliptin or placebo. After 4 weeks the absolute change in RPF due to L-NMMA was smaller in the linagliptin group than in the placebo group (-46.8 ± 34 vs -65.1 ± 36 ml/min, p = 0.045), indicating a lower basal NO activity after treatment with linagliptin. Consistently, the response of UACR to L-NMMA increased in the placebo group (p = 0.059) but not in the linagliptin group (p = 0.276), pointing to an upregulation of NO activity in the placebo group. No clinically meaningful safety concerns were evident.Our data suggest that treatment with the dipeptidyl peptidase-4 inhibitor linagliptin for 4 weeks prevented the impairment of renal endothelial function due to hyperglycaemia in type 2 diabetes.ClinicalTrials.gov NCT01835678 FUNDING: : This study was funded by Boehringer Ingelheim.
EVALuna2:3903